2016
DOI: 10.17265/2161-623x/2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of the Constructivist Learning Approach in Secondary Schools in Kenya: Focus on Learner Achievement in Biology by Class Category

Abstract: Learner achievement is influenced by the instructional methods adopted during the learning process. Different class categories and individual levels present varied learning contexts determining the application of a mixture of appropriate instructional methods, which can enhance knowledge retention and application. Available studies in Kenya have focused on the general achievement of students. This study examined the linkage between instructional methods and learning achievement in different class categories. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The researcher reported that gender influenced the academic achievement of students. In the same vein, Mwanda, Odundo, Midigo, and Mwanda (2016) indicated that female's class performance was enhanced more than the males when the constructivist instructional strategy was employed. However, be it as it may all students had improved academic performance only that the females' performance was overwhelming.…”
Section: Discussionmentioning
confidence: 96%
“…The researcher reported that gender influenced the academic achievement of students. In the same vein, Mwanda, Odundo, Midigo, and Mwanda (2016) indicated that female's class performance was enhanced more than the males when the constructivist instructional strategy was employed. However, be it as it may all students had improved academic performance only that the females' performance was overwhelming.…”
Section: Discussionmentioning
confidence: 96%